No Accelerated Rate of Protein Evolution in Male-Biased Drosophila pseudoobscura Genes - Metta, Muralidhar; Gudavalli, Rambabu; Gibert, Jean-Michel; Schlötterer, Christian (Genetics (Austin), 2006)
Sexually dimorphic traits are often subject to diversifying selection. Genes with a male-biased gene expression also are probably affected by sexual selection and have a high rate of protein evolution. We used SAGE to measure sex-biased gene expression in Drosophila pseudoobscura. Consistent with previous results from D. melanogaster, a larger number of genes were male biased (402 genes) than female biased (138 genes). About 34% of the genes changed the sex-related expression pattern between D. melanogaster and D. pseudoobscura. Combining gene expression with protein divergence between both species, we observed a striking difference in the rate of evolution for genes with a male-biased gene expression in one species only. Contrary to expectations, D. pseudoobscura genes in this category showed no accelerated rate of protein evolution, while D. melanogaster genes did. If sexual selection is driving molecular evolution of male-biased genes, our data imply a radically different selection regime in D. pseudoobscura.